2011
DOI: 10.1007/s10578-011-0264-z
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and Peer Victimisation in Adolescent Girls with Attention-Deficit/Hyperactivity Disorder

Abstract: Emerging evidence suggests that adolescent girls with Attention-Deficit/Hyperactivity Disorder (ADHD) are more socially impaired compared with their peers; however, research has yet to elucidate the nature of this impairment. We investigated overt (e.g., physical, such as hitting or kicking or verbal, such as teasing and taunting) and relational (e.g., social manipulation, such as social exclusion) bullying and victimisation in adolescent girls with and without ADHD. Adolescent girls (mean age = 15.11) with (n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
44
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 54 publications
11
44
1
2
Order By: Relevance
“…It also utilized a rigorously diagnosed, well-characterized and well-retained, ethnically and socioeconomically diverse sample. Findings extend previous research by showing that the increased levels of interpersonal dysfunction and victimization among children and adolescents with ADHD (e.g., Blachman & Hinshaw, 2002; Sciberras et al, 2012; Zalecki & Hinshaw, 2004) persist in the form of physical violence in intimate relationships by early adulthood. In addition, to our knowledge, findings comprise the first evidence regarding physical IPV victimization in women with childhood ADHD, as previous studies examining the IPV-ADHD linkage have focused strictly on IPV perpetration, mostly in males (Fang et al, 2010; Theriault & Holmberg, 2001; Wymbs et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…It also utilized a rigorously diagnosed, well-characterized and well-retained, ethnically and socioeconomically diverse sample. Findings extend previous research by showing that the increased levels of interpersonal dysfunction and victimization among children and adolescents with ADHD (e.g., Blachman & Hinshaw, 2002; Sciberras et al, 2012; Zalecki & Hinshaw, 2004) persist in the form of physical violence in intimate relationships by early adulthood. In addition, to our knowledge, findings comprise the first evidence regarding physical IPV victimization in women with childhood ADHD, as previous studies examining the IPV-ADHD linkage have focused strictly on IPV perpetration, mostly in males (Fang et al, 2010; Theriault & Holmberg, 2001; Wymbs et al, 2012).…”
Section: Discussionsupporting
confidence: 82%
“…For instance, Blachman and Hinshaw (2002) found that school-aged girls with ADHD experienced higher levels of peer conflict and relational aggression than comparison girls (see also Zalecki & Hinshaw, 2004). Sciberras and colleagues (2012) found that adolescent girls with ADHD experienced more overt and relational bullying and peer victimization compared to those without ADHD. Peer relationship dysfunction in youth has been found to be primarily attributable to ADHD rather than to comorbidities, such as oppositional defiant disorder or anxiety disorders (Hoza et al, 2005).…”
mentioning
confidence: 92%
“…For example, preclinical research demonstrates that repeated amphetamine treatment at low doses (1.0 mg/kg) normalizes adult deficits in both behavioral and mPFC DA responses to amphetamine challenge following adolescent social defeat (Burke et al, 2013), which may be related to the reported effect of chronic psychostimulant treatment in decreasing mPFC DAT function (Harvey et al, 2011). Moreover, psychostimulants including amphetamine are routinely given clinically for treatment of attention deficit hyperactivity disorder (ADHD), one of the disorders associated with bullying victimization (Holmberg and Hjern, 2008; Kumpulainen, 2008; Sciberras et al, 2012), and their administration at low doses improves mPFC DA-dependent cognitive task performance in ADHD patients (Arnsten, 2006). Psychostimulants primarily exert their pharmacological effect by blocking catecholamine transporters (NET and DAT; Arnsten, 2006; Fleckenstein et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…9 Özellikle DEHB'li kızlar zorbalığa uğramak konu-sunda daha fazla risk altındadır. 10,11 Literatürde DEHB'li çocuklarda klinik örneklemde yapılmış zorbalık araştırmasına rastlanmamıştır. Literatürde tanı konusunda yapılandırılmış klinik görüşmelerden ölçekler ve geriye dönük kayıtlardan faydalanıl-mıştır.…”
Section: Introductionunclassified